Effectiveness of Endorphin Massage for Pain Reduction During the Active Phase of First-Stage Labor: A Quasi-Experimental Pretest–Posttest Study - Julia Fitrianingsih; Fitriani Fitriani; Dian Meiliani Yulis (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Pain during the first stage of labor frequently heightens maternal stress and may interfere with the physiological progress of childbirth. This study examined the effectiveness of endorphine massage as a non-pharmacological technique for reducing pain experienced by women in the active phase of first-stage labor. A quasi-experimental one-group pretest–posttest design was conducted with sixteen consecutively recruited participants from a community health center. The intervention consisted of a structured endorphine-massage protocol delivered by trained midwives, involving gentle rhythmic strokes and light pressure applied for approximately 15 minutes to the lower back, shoulders, and pelvic area. Pain intensity was measured before and after the intervention using the validated Numeric Rating Scale (NRS). Normality was confirmed with the Shapiro–Wilk test, permitting the use of a paired t-test. The mean pain score decreased from 7.40 before the intervention to 6.13 afterward, indicating a statistically significant reduction (p = 0.001) with a moderate effect size. These findings suggest that endorphine massage may serve as a supportive option for managing pain during the active phase of labor. However, the small sample size and single-site setting limit generalizability, and larger multi-center studies are recommended to strengthen the evidence base for clinical application